Phylogenetic and Evolutionary Genomic Analysis of Listeria monocytogenes Clinical Strains in the Framework of Foodborne Listeriosis Risk Assessment - Gattuso, Antonietta; Cella, Eleonora; Fillo, Silvia; Ortoffi, Marco Francesco; Angeletti, Silvia; Ciccozzi, Massimo; De Medici, Dario; Lista, Florigio; Fiore, Alfonsina (Frontiers in Microbiology, 2022)
Listeria monocytogenes (L. monocytogenes) is one of the most important foodborne pathogens, responsible for listeriosis, a severe disease with symptoms ranging from septicemia, menigoencephalitis and abortion. Given the strong impact of listeriosis on human health and the difficulty of controlling L. monocytogenes along the food production chain, listeriosis has become a priority subjected to molecular surveillance in EU/EEA since 2007. From 2018, surveillance is based on Whole Genome Sequence (WGS) using the core genome Multi Locus Sequences Type (cgMLST). The complete sequences of 132 clinical strains were used to define the evolutionary relatedness among subtypes of L. monocytogenes isolated in Italy from 2010 to 2016, allowed the identification of clades and/or clusters associated with outbreaks or isolated cases of listeriosis. All the strains analyzed fell back in the lineage I and II, and the majority of the strains were classified as lineage II. A probably epidemic entrance in different years for every clades and clusters and from different Region was defined. For the same specific CCs of L. monocytogenes a persistence has been found for long time, this may be related to the fact that some strains are able to survive better than others in food production environment. Phylogenic studies, using WGS data, are able to identify the emergence of highly persistent pathogenic variants, contributing to improve the hazard characterization of L. monocytogenes.